Exploring Preschool Teachers' Perspectives on Pedagogical Integration of Coding in Early Childhood Classrooms - Gusmawanti, Sari; Kurniati, Euis; Mariyana, Rita (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to explore preschool teachers’ perspectives on the pedagogical integration of coding in early childhood classrooms. As coding is increasingly introduced as part of early digital literacy, understanding teachers’ perspectives is essential for designing developmentally appropriate and context-sensitive practices in Indonesian early childhood education.Design/methods/approach – This study employed A qualitative descriptive design to capture teachers’ experiences, interpretations, and classroom considerations regarding coding integration. Five ECE (Early Childhood Education) teachers were selected through purposive sampling based on teaching experience, exposure to digital learning activities, and willingness to participate. Data were collected through semi-structured interviews and analyzed using thematic analysis through transcription, open coding, categorization, and theme development. Trustworthiness was strengthened through member checking, repeated reading of transcripts, and analytic memoing.Findings – The analysis generated eight interrelated themes. Three core findings emerged. First, teachers showed conceptual ambiguity in defining coding, indicating that coding is still understood unevenly in ECE settings. Second, teachers experienced pedagogical tension between digital learning demands and principles of child development, which led to a strong preference for unplugged and play-based coding activities. Third, structural constraints, including limited facilities, insufficient training, and the absence of clear curriculum guidance, restricted consistent implementation. Despite these constraints, teachers recognized coding as potentially beneficial for children’s logical thinking, creativity, problem-solving, and collaboration.Research implications/limitations – This study contributes empirical insight from a developing-country context in which coding in early childhood education remains underexplored. However, The small number of participants and the interview-based design limit broader transferability. Further studies involving more diverse settings, classroom observations, and comparative contexts are needed.Practical implications – The findings underline the need for sustained teacher professional development, accessible teaching resources, and contextual curriculum guidance for play-based coding integration. In low-resource contexts, unplugged coding can function as a realistic pedagogical entry point before the gradual use of digital tools.Originality/value – This study contributes to the discourse on early childhood coding education by foregrounding teachers’ perspectives in the Indonesian ECE context. It positions coding not merely as a technological innovation, but as a pedagogical practice negotiated through developmental considerations and structural limitations.Paper type Research paper